2014
DOI: 10.7314/apjcp.2014.15.18.7849
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Trichostatin A on Anti HepG2 Liver Carcinoma Cells: Inhibition of HDAC Activity and Activation of Wnt/β-Catenin Signaling

Abstract: Purpose: To investigate the effect of deacetylase inhibitory trichostatin A (TSA) on anti HepG2 liver carcinoma cells and explore the underlying mechanisms. Materials and Methods: HepG2 cells exposed to different concentrations of TSA for 24, 48, or 72h were examined for cell growth inhibition using CCK8, changes in cell cycle distribution with flow cytometry, cell apoptosis with annexin V-FTIC/PI double staining, and cell morphology changes under an inverted microscope. Expression of β-catenin, HDAC1, HDAC3, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…This may be associated with an upregulation of Wnt signaling upon exposure to HDAC inhibitors such as VPA and trichostatin A in a patient-dependent manner. Trichostatin A and VPA have been reported to activate Wnt signaling in HepG2 liver carcinoma and Neuro 2A cells [46,47]. This is also demonstrated in breast cancer cell lines where HDAC inhibitors have been found to upregulate b-catenin expression leading to increased Wnt signaling [29].…”
Section: Discussionmentioning
confidence: 87%
“…This may be associated with an upregulation of Wnt signaling upon exposure to HDAC inhibitors such as VPA and trichostatin A in a patient-dependent manner. Trichostatin A and VPA have been reported to activate Wnt signaling in HepG2 liver carcinoma and Neuro 2A cells [46,47]. This is also demonstrated in breast cancer cell lines where HDAC inhibitors have been found to upregulate b-catenin expression leading to increased Wnt signaling [29].…”
Section: Discussionmentioning
confidence: 87%
“…Studies have indicated that the overexpression of cyclin D1 may result in a reduction of the G1 phase of the cell cycle (15)(16)(17), leading to progression into the S phase and completing the duplication of DNA. The increase in the protein expression of cyclin D1 is observed in certain primary malignant tumors, including parathyroid adenoma, neck squamous-cell carcinoma, breast cancer, esophageal cancer, and hepatocellular carcinoma (18)(19)(20)(21). As MAPK is expressed as an upstream gene of cyclin D1, the increase in the level of p-MAPK in osteosarcoma was directly proportional to the intensity of cyclin D1-positive staining.…”
Section: Discussionmentioning
confidence: 99%
“…Cyclin D1 forms a complex with cyclin-dependent kinases 4 and 6 and functions as a regulatory subunit of this complex. Cyclin D1 is required to facilitate the transition between G1 and S phases; therefore, it promotes the proliferation of cells and may contribute to tumorigenesis ( 23 , 24 ). In addition, cyclin D1 acts as a downstream effector molecule for Wnt/β-catenin signaling.…”
Section: Discussionmentioning
confidence: 99%